Universal Humanity as Discourse of Nationalism in Garin Nugroho’s Soegija (2012) - Fredy Nugroho Setiawan; M. Andhy Nurmansyah; Rizki Nufiarni; Scarletina Vidyayani Eka (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2021)
This research discusses discourse of nationalism in Garin Nugroho’s Soegija, a biopic which premiered in 2012. The film is chosen because it presents the story of Soegijapranata, an intellectual who is not from dominant nationalist groups, during the era of independence movement; he is neither a prominent military figure nor a figure from the largest religious group in Indonesia. This film is analyzed to investigate its position in ideological contestations emerging after the Reformation, particularly after the 2000s. Seymour Chatman’s postulates regarding story and discourse in narrative structure of fiction and film (1978) is used as a theoretical framework for this research. The results show that discourse of nationalism is presented in the narrative structure of the film in the form of arguing the idea of universal humanity in the context of Indonesia as a nation. This effort is portrayed by the main character’s intellectual struggles against shallow primordialism that influences both Indonesian people’s perspectives during independence movement era and foreign people’s point of views, the colonizers, which are represented by subversive actions of the Dutch and Japanese in Indonesia. The values of universal humanity that have been adopted into the spirit of nationalism are stated through the main characters’ statements and actions. It can be concluded that the concept of nationalism in Indonesia is said to be born from a long struggle against oppression and injustice. This concept has become a dominant ideology which remains relevant, as implied in Soegija.